ANTI-INFLAMMATORY ACTIVITY OF PAEDERIA FOETIDA LINN IN CARRAGEENAN INDUCED RAT PAW EDEMA - Bandiya , Meena; Dashora, Kamlesh; Sisodiya, Dharmesh (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2022)
Ancient time herbal medicine are used for diagnosis of many disease use of natural restoration for prevention and removal of disease symptoms . Although both ethanolic extract and butanolic fraction are effective against carrageenan induced paw edema but butanolic fraction was more effective then its ethanolic extract.Finaly accomplished butanolic fraction of ethanolic extract 100 mg produce a significant anti-inflammatory effects than phenylbutazone 50 mg and ethanolic extract 200 mg. occurs 4 to 5 hrs. after carrageenan injection their acceptability in modern system of medicine . One of the major problems faced by the herbal industry is the unavailability of rigid quality control profiles for herbal materials and their formulations. QC of herbal drugs should meet the standards related to safety, potency and efficacy. There are some specific system present in human body that is responsible for controlling brain heamostatis as well as heamolytic factors. these factor are extradude there effect in the form of adverse reaction role The inflammatory activity against carrageenam induced paw edema in rat using pet ether extract and ethanolic are effective but aqueous extract was more effective as compare to Pet.ether and ethanolic extract. All three extract having analgesic activity but aqueous fraction has more analgesic activity in camparision of Pet ether and ethanol extract . In conclusion every that the plant extracts possess anti- inflammatory and analgesic properties and lead to the isolation of novel compounds.